Intramedullary nailing of tibial non-unions using the suprapatellar approach: a case series - Botma, Nicolaas (Division of Orthopaedic Surgery, 2022)
Background: A number of treatment options are available for diaphyseal non-unions of the tibia, including intramedullary (IM) nailing. An infrapatellar entry point with the knee in deep flexion can make this procedure challenging, especially with associated deformity or an obliterated canal. The suprapatellar approach allows nail insertion with the knee extended, which facilitates correction of malalignment in the sagittal and coronal planes. The aim of our study was to review the outcome of diaphyseal tibia non-unions, treated with an intramedullary nail, using the suprapatellar approach. Method: We retrospectively reviewed consecutive cases with non-union of the tibial shaft, treated with a suprapatellar entry nail between May 2016 and January 2018. Patients who were previously managed with a nail or who had active sepsis were excluded. The rate and time to union, as well as complications were assessed. Results: Thirteen cases were included and followed up until union at a mean of 5.8 months. All were performed percutaneously, without opening of the non-union site. Two patients developed complications, although bony union was still achieved. Conclusion: A suprapatellar entry tibial nail is an acceptable treatment option for tibial non-unions not previously treated with a nail.